UMPSA hosts Jom Masuk U Zon Timur II Programme - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 27 May 2024 - The Jom Masuk U 2024 (JMU2024) Zon Timur II Programme organised by the Ministry of Higher Education (MOHE) in strategic collaboration with Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) on 1 and 2 June 2024 will be the focus by targeting 20,000 visitors to attend the UMPSA Sports Complex Hall at Gambang Campus.